Seduhan Kunyit (Curcuma Domestika Val) Terhadap Nyeri Gastritis - Maharani Farah Dhifa Dg Masikki; Marsuji Utami; Sri Yulianti (Indonesian Journal of Innovation Multidisipliner Research, 2024)
Gastritis is called gastric pain or maag in Indonesian words. This disease will be dangerous if not be treated well, it caused gastric ulcer and risk for cancer and death even. The Curcuma Domestica Val Infusion have good effect for cure process because it mostly consume for inflamation disease, ulcer and abdominal upset. The aims of research to anlyse the influences of curcuma domestica val infusion toward gastritis pain in Bunga Merpati Clinic, Palu. This is quantitative research with quasy experiment method and one group pre and post test without control design. Total of population is 31 gastritis patients and sampling only 13 people. Data analysed by Wilcoxon Signed Rank Test with curcuma domestica val infusion administered as a independent variable and gastric pain as a dependent variable. The result of research found P value = 0,001, so it means that have influences of curcuma domestica val infusion administered toward gastritis pain in Bunga Merpati Clinic, Palu. Before administered of curcuma domestica val infusion, most of respondents have severe gastric pain, but after it most of them have slight gastric pain. Conclusion mentioned that have influences of curcuma domestica val infusion administered toward gastritis pain in Bunga Merpati Clinic, Palu.